Preserving the Gobi: Identifying potential UNESCO world heritage in Mongolia's Gobi desert - McCarthy, C. (2022)
The Gobi Desert, Asia's largest desert, covers roughly 1,300,000 square kilometers across southern Mongolia and northern China. One of the world's most iconic deserts, the Gobi is a functioning, healthy ecosystem home to spectacular landscapes that support an impressive variety of biological diversity, including many rare and endangered species. Human activity in the Gobi has existed for at least 5,000 years and several culturally and historically significant archeological sites have been documented in the region; the Gobi continues to support an ancient and enduring nomadic lifestyle. Prehistoric traces of ancient life are also widespread, making the Gobi a hotspot for fossil discoveries. Despite a wealth of natural and cultural heritage the Gobi Desert in Mongolia lacks any recognition as UNESCO World Heritage. This article explores the natural and cultural heritage of the Gobi Desert in Mongolia and using UNESCO's framework for “Outstanding Universal Value,” identifies several sites with exceptional geological, ecological, and ethnological features that we believe meet the criteria for World Heritage status. In the face of looming threats from human interference and climate change, increased recognition and appreciation of Gobi Desert landscapes is crucial to ensure the long-term protection of these irreplaceable sources of life and inspiration.